2020
DOI: 10.1080/00220973.2020.1799312
|View full text |Cite
|
Sign up to set email alerts
|

Domain-general and math-specific self-perceptions of perseverance as predictors of behavioral math persistence

Abstract: Three studies examine a novel pathway by which the perseverance component of the personality trait grit might predict college students' behavioral persistence when solving challenging math problems. Specifically, we focus on the intervening role of what we refer to as math-specific selfperceptions of perseverance, which captures students' perceived tendency and ability to persevere on challenging math problems. Across studies, we found that this math-specific construct was correlated with behavioral math persi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
0
6
1
Order By: Relevance
“…Likewise, studies involving secondary school students have shown the same impact where grit was found to affect the mathematical achievement of students (Al-Mutawah & Fateel, 2018;Carson, 2020;Datu et al, 2021;Khan, 2018;Orogo, 2022;Yu et al, 2021). In addition, studies by (Bowen, 2018;Chen & Gong, 2021;Flanagan & Einarson, 2017;Miele et al, 2022), which were conducted on university students have also emphasized the importance of grit in the achievement of mathematics. Overall, the findings of past studies in relation to Mathematics education clearly show that grit has a significant impact on academic achievement in general and on Mathematics in particular.…”
Section: Literature Reviewmentioning
confidence: 88%
See 2 more Smart Citations
“…Likewise, studies involving secondary school students have shown the same impact where grit was found to affect the mathematical achievement of students (Al-Mutawah & Fateel, 2018;Carson, 2020;Datu et al, 2021;Khan, 2018;Orogo, 2022;Yu et al, 2021). In addition, studies by (Bowen, 2018;Chen & Gong, 2021;Flanagan & Einarson, 2017;Miele et al, 2022), which were conducted on university students have also emphasized the importance of grit in the achievement of mathematics. Overall, the findings of past studies in relation to Mathematics education clearly show that grit has a significant impact on academic achievement in general and on Mathematics in particular.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Studies related to grit have been conducted globally since it was introduced by (Duckworth, 2007). Some of the most recent studies on grit and Mathematics include those by (Al-Mutawah & Fateel, 2018;Chen & Gong, 2021;Datu et al, 2021;Eryiğit & Kılıç, 2022;Kaya & Karakoc, 2022;Miele et al, 2022;Orogo, 2022;Yu et al, 2021). Studies by (Eryiğit & Kılıç, 2022;Kaya & Karakoc, 2022) focus on primary school students towards Mathematics and grit thinking as well as grit and academic achievement during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Acknowledging that "more competent individuals may find solutions more quickly than less competent individuals" (Shen et al, 2016, p. 42), a survey was created by the first author, inspired by the work of other researchers (Brown & Inouye, 1978;Jacobs et al, 1984;Miele et al, 2022;Shen et al, 2016). The survey included one impossible task placed at the end of the survey, and other tasks measuring factors such as self-efficacy.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of the impossible task was to measure persistence. As in prior research (Brown & Inouye, 1978;Jacobs et al, 1984;Miele et al, 2022;Shen et al, 2016), we measured persistence by quantifying the time a student spent working on a given task. The task reads as follows:…”
Section: Methodsmentioning
confidence: 99%